Comparative characteristics of vasopressinergic neurons of the supraoptic and paraventricular nuclei of hypothalamus response in the intermittent hypoxic hypoxia - A. V. Abramov; V. O. Shamenko; Yu. M. Kolesnyk (Zaporozhye State Medical University, 2018)
The vasopressinergic system of the hypothalamus occupies an important place in the neuroendocrine mechanisms of maintaining homeostasis, controlling autonomic reactions and the processes of adaptation of the organism to the acute and chronic stressors. The main portion of the magnocellular vasopressin-synthesizing neurons is localized in the supraoptic nucleus (SON) and in the lateral part of the posterior magnocellular subnuclei of the paraventricular nucleus (PVNpml). The aim of study was to establish the features of the vasopressinergic neurons of the hypothalamus magnocellular nuclei functional state under the inflence of prolonged intermittent hypoxic hypoxia and in the post-hypoxic period. Materials and methods. The research was carried out on 30 male Wistar rats. Intermittent hypoxia was modeled by daily 6 hour stay of rats at the simulated altitude of 6000 m (pO2 = 9.8 %) for 15 days, the post-hypoxic period lasted 10 days. The distribution of [Arg8]-vasopressin (AVP), cFos, HIF-1α, and HIF-3α proteins was investigated by quantitative immunoflorescence methods in serial frontal sections of hypothalamus. Results. The hypoxic hypoxia action led to SON neurons degeneration, inhibition of AVP synthesis in SON by 40 %, decrease of cFos protein content by 56 %, and the failure of reaction to hypoxia from the HIF-proteins family. In PVNpml neurons, intermittent hypoxia stimulated 6-fold increase in the AVP content along with cFos-protein increase by 80%. The response of PVNpml neurons to hypoxia was accompanied by 3-times increase of the HIF family proteins content. In the post-hypoxic ially restored in SON neurons, but decrease of cFos-protein synthesis indicated inhibition of secretory activity in SON. In the post-hypoxic period the content of the AVP and the HIF-proteins decreased signifiantly in PVNpml neurons, but the level of all proteins remained higher than in the control group. At the same time, the level of cFos secretory activity did not change signifiantly as compared with the hypoxic period. These data indicate the stability of the high level of functional activity of the PVNpml asopressinergic neurons during the 10-day post-hypoxic period. Conclusions. Intermittent hypoxia stimulates the functional activity of the PVNpml that manifests as an increase of vasopressin, cFos, HIF-1α, and HIF-3α proteins synthesis in magnocellular neurons. In the post-hypoxic period, a slight decrease in the synthesis of vasopressin, HIF-1α and HIF-3α proteins is observed without a decrease in the cFos protein content in PVNpml. Intermittent hypoxia inhibits the functional activity of SON neurons, which is partially restored in the post-hypoxic period.